(untitled) - Mustafa Hamed Abdullah Mahmoud Al-Mahlawi, Assist. Prof. Dr. Abdullah Hamid Hussein Al Dulaimi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research aims to show the approach of Abdul-Kamal Al-Trauniki in his book: Al-Namliah in showing the morphological and grammatical rules, which is a book specialized in the grammar of the Arabic language, in grammar, morphology, and language. The third in letters. It has investigated and studied the two chapters: the first and the second. This research is part of my study of the book Al Namliyah, and I explained the author's approach by dividing it into five sections: Section One: Linguistic issues The second section: morphological issues. The third section is grammatical issues. Section IV: Rhetorical issues. Section Five: Miscellaneous Issues. In each point I mention, I give two or more examples from the verified text, and mention in the margin the verified text a page like this, then follow it with a referral to the approved sources.